PENGARUH MOTIVASI KERJA GURU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KEDISIPLINAN GURU SD DI TAMBAKROMO PATI - Roikatus Sa’diyah; Su’ad; Gunawan Setiadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The objectives of this study were: (1) analyzing the effect of work motivation on the discipline of elementary school teachers in Kecamatan Tambakromo, Kabupaten Pati; (2) analyzing the effect of principals' leadership on the discipline of elementary school teachers in Kecamatan Tambakromo, Kabupaten Pati; (3) analyzing the effect of work motivation and principals' leadership on the discipline of elementary school teachers in Kecamatan Tambakromo, Kabupaten Pati. This research was quantitative research which was classified as correlational research. This research aimed to seek the influence of teacher work motivation (independent variable, X1) and principals’ leadership (independent variable, X2) towards teachers' discipline (dependent variable, Y). The research was conducted from July to August 2020 at 32 public elementary schools throughout Kecamatan Tambakromo. The total population was 204 people, and 150 samples were randomly selected. The data were collected using questionnaires. It was found that the data were normally distributed, homogeneous, linear, and not multicollinear. The hypothesis test obtained: (1) there was a relationship between variable X1 and Y with the equation Y = 36.851 + 0.345X1, so the hypothesis was accepted. It indicated that every increase of one unit of work motivation increased teachers' discipline by 0.345 at a constant of 36.851, and the strength of the correlation was 0.670. The percentage contribution of variable X1 to Y was 55.2%; (2) there was a relationship between variable X2 and Y with the equation Y = 36.851 + 0.395X2. The correlation score was 0.680 with a contribution of 57.8%; (3) there was a positive relationship between work motivation and principals' leadership on teachers' discipline which was stated by the equation Ŷ = 36.851 + 0.345X1 + 0.395X2. The correlation score was 0.707. Finally, the contribution of variables X1 and X2 to Y was 49.9%, while 50.1% was influenced by other factors.